Hepatitis B outbreak at Glenochil prison during January to June 1993. - Hutchinson, S. J. (Cambridge University Press, 1998)
This data linkage study examined the extent of hepatitis B transmission and co-infection with HIV among 636 former inmates of Glenochil prison, Scotland, during an outbreak of bloodborne diseases in 1993 which was related to needle sharing. Eleven inmates imprisoned during the first half of 1993 presented with hepatitis B infection, of whom co-infection with HIV was detected in six. Based on dates of test results in relation to time of imprisonment, seven definitely acquired their hepatitis B infection within the prison. Only two infections were reported to Scotland's hepatitis B register and neither could be prison-linked. This outbreak of hepatitis B is the first of its kind to be reported but not the first to have occurred. It not only highlights the urgency for measures to prevent further spread of infection among prisoners but also illustrates the need for comprehensive surveillance of hepatitis B infection, and the need for a protocol on how to manage such outbreaks and on how to establish the extent of transmissions when acute hepatitis B occurs in prison.